Genetic relatedness of low solitary nests of Apis dorsata from Marang, Terengganu, Malaysia - Abd Manaf, Ali; Najmeh Sahebzadeh, Marden; Soon, Guan Tan; Nur Azura, Adam
Knowledge on the population of genetic structure and ecological behaviour of Apis dorsata from Peninsular Malaysia is needed for effective management and conservation of this species since unsustainable whole solitary low nest cutting for product harvesting is the current common practice here The analysis of 15 single locus DNA rnicrosatellite markers on samples from 20 solitary nests of A dorsata showed that while these markers were polymorphic, high intracolonial relatedness existed Furthermore, in general slightly negative values of intercolony relatedness (R) among the nests of A. dorsata were found However, positive values of mean intercolony relatedness were observed between 54 pairs of nests out of 190 possible combinations The R values among nest pairs 3-4 and 3-5 was higher than 0 50 showing that their queens were half siblings. whereas nest pair 19-20 showed relatedness of 0.95 indicating that the same queen was sampled. The results that we obtained could not conclusively support the hypothesis of this study that the honey hunters in Marang district of Malaysia repeatedly harvest the same nest located at a different site and at a different time during the same honey harvesting season However. our finding of an appreciable level of intercolonial relatedness between several pairs of nests in this pioneer study indicated that a comprehensive study with a larger sample size of solitary nests found throughout the region would be necessary to provide concrete proof for this novel idea Ci 2012 Sahebzadeh et al.